2021
DOI: 10.4049/jimmunol.2001002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mast Cell Degranulation Mediated by Purinergic Receptors’ Activation and PI3K Type δ

Abstract: The potential role of purine nucleotides in the function of human lung mast cells under physiological and pathophysiological conditions was originally conceived by A.P. and E.S.S. H.N. conducted all experiments and was assisted by F.N. H.N. and A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The LAD2 human-derived MC line was developed at the NIH from a patient with systemic mastocytosis ( 5 , 6 , 10 ). As recently reported, LAD2 cells express five P2YRs (P2Y1, P2Y6, P2Y11, P2Y12, and P2Y14) along with three P1Rs (A2aR, A2bR, and A3R), and two P2XRs (P2X1 and P2X7) ( 59 ). LAD2 cells express CD39 but not CD73, suggesting extracellular nucleotides could be degraded to AMP but not to adenosine ( 59 ).…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…The LAD2 human-derived MC line was developed at the NIH from a patient with systemic mastocytosis ( 5 , 6 , 10 ). As recently reported, LAD2 cells express five P2YRs (P2Y1, P2Y6, P2Y11, P2Y12, and P2Y14) along with three P1Rs (A2aR, A2bR, and A3R), and two P2XRs (P2X1 and P2X7) ( 59 ). LAD2 cells express CD39 but not CD73, suggesting extracellular nucleotides could be degraded to AMP but not to adenosine ( 59 ).…”
Section: Introductionmentioning
confidence: 62%
“…ATP is unimodal, only enhancing degranulation, whereas adenosine is bimodal; at high concentrations, it inhibits degranulation and at low concentrations, it potentiates degranulation. At equimolar concentrations, ATP is more potent than adenosine in enhancing HMC degranulation ( 57 – 59 ). ATP’s enhancing effects on IgE-mediated degranulation in freshly isolated HLMC, without exposure to varied cytokine mixtures over days to weeks in cultures, is substantial and reproducible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular ATP activated ionotropic P2X4 receptors and enhanced antigen-triggered degranulation potentiating a high affinity IgE receptor (FceRI)mediated tyrosine kinase signaling cascade. Among multiple P2Y receptor subtypes, the P2Y 11 receptor was involved in degranulation enhancement via the PI3K/protein kinase B pathway (204). Studies in rhesus macaques, that presented authentic mild to moderate forms of COVID-19 (205), have shown that SARS-CoV-2 triggered mast cell degranulation induced acute alveolar epithelial inflammation and lung injury and that prophylactic administration of MC stabilizers that blocked degranulation could dampen the SARS-CoV-2 response and prevent lung injury (206).…”
Section: Purinergic Targets For Sars-cov-2 Induced Pathologiesmentioning
confidence: 99%